Hermeneutika Sebagai Jalan Teologi Pembebasan Farid Esack - Syafrinal Randa (Fakultas Ushuluddin, Universitas Darussalam Gontor, 2023)
Liberation theology is a theological view that was born and developed as a self-liberation movement or group from oppression. Liberation theology is also a phenomenological discourse with plural social conditions and experiencing oppression and inequality that restrain religious adherents. Farid Esack, a South African intellectual who was in the Apartheid regime, held the view that believers should not submit to political authority and discriminatory social conditions of society. In this social condition, Farid Esack saw the need to reinterpret the Qur'an using hermeneutics as an approach. Through the concept of hermeneutics, he is able to give rise to new ideas about theology or what he calls liberation theology. This is an effort to answer existing social problems, especially in South Africa. The writing of this article uses the library research method with a literature study approach, which is carried out by collecting and analyzing information from written sources such as books, journals, articles, and documents related to the topic discussed. According to Farid Esack, the concept of hermeneutics is very necessary considering that the books in religion are not only a teaching concept that only contains rituals but also contains universal human liberation from social inequality and oppression.